Control of pH for separated quantitation of nitrite and cyanide ions using photoluminescent copper nanoclusters. Issue 36 (7th September 2017) - Cang, Jinshun; Wang, Chia-Wei; Chen, Po-Cheng; Lin, Yi-Jyun; Li, Yu-Chi; Chang, Huan-Tsung
Abstract : A dual sensing probe for quantitation of NO2 − and CN − ions. Abstract : A dual sensing probe has been developed for the detection of nitrite (NO2 − ) and cyanide (CN − ) ions based on the analyte-induced photoluminescence (PL) quenching of thiosalicylic acid (TA) capped-copper (Cu) nanocluster (NC) aggregates. The TA–Cu NC aggregates prepared from Cu 2+ and TA emit at 420 nm when excited at 338 nm, with a quantum yield of 13.2%. The PL quenching of the TA–Cu NC aggregates by NO2 − is through a redox reaction between HNO2 and TA under acidic conditions, while that by CN − ions in a basic solution is through an etching process. By controlling pH values at 5.0 and then at 8.0, the probe allows consecutive quantitation of NO2 − and CN − ions in water samples, with limits of detection of 5 μM and 5 nM, respectively, at a signal-to-noise ratio of 3. The practicality of this probe has been validated through the determination of the concentrations of NO2 − and CN − ions in representative lake water samples.